Blood pressure patterns in rural, semi-urban and urban children in the Ashanti region of Ghana, West Africa - Owusu-Dabo Ellis; Redekop William K; Agyemang Charles; Bruijnzeels Marc A (BMC, 2005)
Abstract Background High blood pressure, once rare, is rapidly becoming a major public health burden in sub-Saharan/Africa. It is unclear whether this is reflected in children. The main purpose of this study was to assess blood pressure patterns among rural, semi-urban, and urban children and to determine the association of blood pressure with locality and body mass index (BMI) in this sub-Saharan Africa setting. Methods We conducted a cross-sectional survey among school children aged 8-16 years in the Ashanti region of Ghana (West-Africa). There were 1277 children in the study (616 boys and 661 females). Of these 214 were from rural, 296 from semi-urban and 767 from urban settings. Results Blood pressure increased with increasing age in rural, semi-urban and urban areas, and in both boys and girls. The rural boys had a lower systolic and diastolic blood pressure than semi-urban boys (104.7/62.3 vs. 109.2/66.5; p < 0.001) and lower systolic blood pressure than urban boys (104.7 vs. 107.6; p < 0.01). Girls had a higher blood pressure than boys (109.1/66.7 vs. 107.5/63.8; p < 0.01). With the exception of a lower diastolic blood pressure amongst rural girls, no differences were found between rural girls (107.4/64.4) and semi-urban girls (108.0/66.1) and urban girls (109.8/67.5). In multiple linear regression analysis, locality and BMI were independently associated with blood pressure in both boys and girls. Conclusion These findings underscore the urgent need for public health measures to prevent increasing blood pressure and its sequelae from becoming another public health burden. More work on blood pressure in children in sub-Saharan African and other developing countries is needed to prevent high blood pressure from becoming a major burden in many of these countries.